O corpo e a mente em um estado de equilíbrio: a cirurgia bariátrica na moda - Frizo, Caroliny Fernanda (2016)
This project aims to analyze the individual's body after bariatric surgery, and thereby cause a reflection of fashion and art for better understanding and appreciation of beauty installed in this new body, to develop a garment that meets their psychological needs and physiological after surgery. Morbid obesity is shown in episodes of comorbidities and psychological disorders such as depression and social phobia. The methodology for developing this study was to literature, it will be the qualitative approach with individuals who have surgery, looking for ways to better serve this audience that is moved in the market and society. It is expected this work, contribute to the development of the individual and his, elevating his character and his personality, bringing their self-esteem and identity.